(untitled) (Research, Society and Development, 2021)
This paper aims to analyze the legal advances and challenges regarding the effectiveness of the child’s right to early childhood education in the city of João Pessoa / PB. The advances in educational legislation that have moved towards ensuring education as a subjective right for everyone and an essential element for material and cultural construction do not negate the need for a better understanding of how this right has been realized for children, specifically in early childhood education. Therefore, the problem question analyzes how the right of children to Early Childhood Education in the Municipality of João Pessoa (PB) has been taking place. To this end, it is brought as theoretical support about the child’s right to education Dias (2008), Ruiz (2007) and Fernandes & Candau (2017). In order to achieve the proposed objective and using qualitative, documentary and bibliographic research as a methodological path, the study focused on official documents, current national legislation on early childhood education and observation of official data that portray the educational scenario. As a result, within the scope of the municipality of João Pessoa / Paraíba, it appears that, despite the significant advances, the current panorama reveals the gap in the provision of early childhood education, as well as the failure to fully realize the right to education for little child.